Goal Setting Training to Improve Future Orientation in the “The Lost Boys” Community - Febriani, Lailatul Fitrih; Noviekayati, I Gusti Ayu Agung (Yayasan Sinergi Kawula Muda, 2025)
This study aims to determine the effectiveness of goal setting training in improving future orientation among the youth community known as “The Lost Boys” in Randutatah Village, Paiton District, Probolinggo Regency. The method used is psychological intervention with a participatory training approach through five sessions, namely opening, future inspiration, self-potential exploration, goal setting, and closing. The results of the study showed positive changes in the participants after attending the training, where they began to be able to recognize their potential, set short-term and long-term goals, and show increased motivation and productive behavior such as reducing risky behavior, stopping alcohol consumption, and being active in social activities. This training also helped participants understand the importance of having a clear direction in life and responsibility for the future. Overall, goal setting training has proven to be effective as a psychological intervention strategy for shaping a positive future orientation, increasing self-awareness, and fostering a commitment to change in at-risk adolescents. Implementation can be enhanced through continuous mentoring, collaboration with community leaders, and integration into youth empowerment programs to sustain behavioral change. Future efforts should expand participation, involve family and peers, and use digital media for ongoing motivation and goal tracking. This study provides a novel community-based application of goal-setting training among at-risk rural youth in Indonesia, a population rarely addressed in previous intervention research.